2022
DOI: 10.3390/molecules27196322
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, Theoretical Calculations, Antibacterial Activity, Electrochemical Behavior, and Molecular Docking of Ni(II) and Cu(II) Complexes with Pyridoxal-Semicarbazone

Abstract: New Ni (II) and Cu (II) complexes with pyridoxal-semicarbazone were synthesized and their structures were solved by X-ray crystallography. This analysis showed the bis-ligand octahedral structure of [Ni(PLSC-H)2]·H2O and the dimer octahedral structure of [Cu(PLSC)(SO4)(H2O)]2·2H2O. Hirshfeld surface analysis was employed to determine the most important intermolecular interactions in the crystallographic structures. The structures of both complexes were further examined using density functional theory and natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 68 publications
9
9
0
Order By: Relevance
“…Overall, the molecular docking results revealed that the H 2 BETSC ligand and its complexes show promising activity toward the proteins under investigation comparable to those of reported literature [52–55] . And they exhibit a significant binding on the 1KZN protein more than 5ZHZ binding protein.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Overall, the molecular docking results revealed that the H 2 BETSC ligand and its complexes show promising activity toward the proteins under investigation comparable to those of reported literature [52–55] . And they exhibit a significant binding on the 1KZN protein more than 5ZHZ binding protein.…”
Section: Resultssupporting
confidence: 79%
“…Overall, the molecular docking results revealed that the H 2 BETSC ligand and its complexes show promising activity toward the proteins under investigation comparable to those of reported literature. [52][53][54][55] And they exhibit a significant binding on the 1KZN protein more than 5ZHZ binding protein. Among the studied compounds the [Co(H 2 BETSC) 2 showed better binding affinities to topoisomerase II (1KZN) and topoisomerase IV (5ZHZ).…”
Section: Chemistryselectmentioning
confidence: 99%
“…It is noteworthy that, in all complexes, the ligand is in zwitterionic form with the protonation of the N1 nitrogen pyridine ring and deprotonation of the O2 atom, as reported in the literature for other similar metal complexes with pyridoxal ligands ( Jevtovic et al, 2023 ; Jevtovic et al, 2022 ). The value found between 123.7 (7) and 125.3 (2)° for the bond angle C3–N1–C4 indicates the presence of a proton on the N1 atom, as this angle has been observed for deprotonated forms of similar ligands with the value of about 118° ( Jevtovic et al, 2022 ).…”
Section: Resultssupporting
confidence: 60%
“…It is noteworthy that, in all complexes, the ligand is in zwitterionic form with the protonation of the N1 nitrogen pyridine ring and deprotonation of the O2 atom, as reported in the literature for other similar metal complexes with pyridoxal ligands ( Jevtovic et al, 2023 ; Jevtovic et al, 2022 ). The value found between 123.7 (7) and 125.3 (2)° for the bond angle C3–N1–C4 indicates the presence of a proton on the N1 atom, as this angle has been observed for deprotonated forms of similar ligands with the value of about 118° ( Jevtovic et al, 2022 ). Comparing the free ligand PLBHZ ( Back et al, 2009 ) with complexes (1–4), the bond distances found N2–N3 between 1.370 (8) and 1.387 (3)° and C9-O3 between 1.235 (9) and 1.259 (4)° are indicative of some electron delocalization throughout the hydrazone function with the coordination of the N3 and O3 atoms to the metal centers.…”
Section: Resultssupporting
confidence: 60%
“…Given its two essential functions in metabolism and iron acquisition, the E4PDH enzyme from A. baumannii may be critical in bacterial pathophysiology [ 128 ]. In addition to vitamin B6 derivatives, metals such as gold [ 130 ], nickel, copper [ 131 ] and gallium [ 132 ] are employed. Metal complexes were investigated for their potential antibiotic efficacy against various bacterial strains, and the results against resistant bacteria were encouraging.…”
Section: Novel Therapeutic Agentsmentioning
confidence: 99%